Descending dragon, rising tiger : a history of Vietnam - Lien, Vu Hong (Reaktion Books, 2014)
Outside of its war with the United States, Vietnam's past has often been neglected and understudied. Whether as an aspiring subordinate or a rebel province, Vietnam has been viewed by most historians in relation to its larger neighbor to the north, China. Seeking to reshape these accounts, Descending Dragon, Rising Tiger chronicles the vast sweep of Vietnam's tumultuous history, from the Bronze Age to the present day, in order to lay out the first English-language account of the full story of the Vietnamese people. Drawing on archeological evidence that reveals the emergence of a culturally distinct human occupation of the region up to 10,000 years ago, Vu Hong Lien and Peter D. Sharrock show that these early societies had a sophisticated agricultural and technological culture much earlier than previously imagined. They explore the great variety of cultures that have existed in this territory, unshackling them from the confined histories of outsiders, imperial invaders, and occupiers in order to show that the country has been central to the cultural, political, and ethnic development of Southeast Asia for millennia. Unrivaled in scope, this comprehensive account will be the definitive history of the Vietnamese people, their culture, and their nation.